Construction of anti-HER2 affibody-directed CAR-NK and its synergistic effects with doxorubicin-loaded nanodrug against HER2-positive breast cancer - He, Xuesong; Liang, Zhaoyuan; Liu, Qing; Zhang, Xiaofei; Liang, Hao; Jia, Runqing; Sheng, Wang (Frontiers in Immunology, 2026)
IntroductionChimeric antigen receptor (CAR)-engineered T or natural killer (NK) cells are a promising approach for cancer immunotherapy. The leading region of the CAR structure is generally a single-chain antibody (scFv) fragment specific for a tumor cell surface molecule, and other structures are rarely reported.MethodsIn this study, we developed a novel anti-human epidermal growth factor receptor 2 (HER2) CAR-NK cell using an affibody molecule as the extracellular targeting domain instead of a conventional scFv. Affibody-based CAR-NK cells were generated from the NK-92 cell line. To enhance safety, CAR-NK cells were subjected to γ-irradiation, and their antitumor activity was further evaluated in combination with doxorubicin (DOX)-loaded nanoparticles.ResultsAffibody-based CAR-NK cells exhibited effective cytotoxicity against HER2-positive breast cancer cells, comparable to that of anti-HER2 scFv-based CAR-NK cells. γ-Irradiation at 10 Gy effectively inhibited malignant proliferation of CAR-NK cells but significantly reduced their cytotoxic activity. Notably, incorporation of DOX-loaded nanoparticles markedly enhanced the killing capacity of irradiated CAR-NK cells, restoring and even amplifying their antitumor efficacy.DiscussionThese findings demonstrate that affibody-based CAR-NK cells are a viable alternative to conventional scFv-based CAR constructs. Moreover, the combination of CAR-NK immunotherapy with chemotherapeutic nanomedicine effectively compensates for irradiation-induced cytotoxicity attenuation, offering a promising synergistic strategy for the treatment of HER2-positive breast cancer.